Implementasi Pendidikan Karakter Melalui Pembelajaran Sentra Pada AUD Di Kelas B TK Nurhidayah Barru - Fitri, Riskal; Indahyanti, Rizka (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
This research used a qualitative case study design. The purpose of this research was to determine the implementation of character education through center learning, to find out the weaknesses of teachers in implementing character education in the center learning model, and to overcome the weaknesses of teachers in implementing character education through the center learning model. The object of this research is class B of TK Nurhidayah Barru. The efforts made in this research are by observing the playing activities carried out by the teacher in each center learning which includes the preparation center, development center, natural art, and religion. The data collection techniques used were interviews, teacher and student observation, and documentation. The results showed that the implementation of character education through the center learning model applied in the TK Nurhidayah Barru teachers was to build an attitude of independence, mutual respect, cooperation, sincerity, honesty, and compassion.